1995
DOI: 10.1111/j.1476-5381.1995.tb13298.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular 5‐HT1‐like receptors mediating vasoconstriction and vasodilatation: their characterization and distribution in the intact canine cardiovascular system

Abstract: 1 In anaesthetized dogs, intra-left atrial administration of 5-hydroxytryptamine (5-HT) and selected tryptamine analogues (5-carboxamidotryptamine, 5-CT; 5-methyl tryptamine, 5-MT; a-methyl 5-hydroxytryptamine, a-HT; sumatriptan, Sum) in the presence of ketanserin and MDL72222 (5-HT2 and 5-HT3 receptor antagonists, respectively), produced dose-related changes in carotid, coronary 5 The coronary (and carotid) vasodilator responses to 5-CT were antagonized by the 5-HTI-like receptor antagonists, spiperone (1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…By contrast, in the renal vascular beds, sumatriptan and 5-carboxamidotryptamine both produced marked vasoconstrictor responses, which were characterized by a very rapid recovery and evidence of a secondary vasodilatation (Cambridge et al, 1991a,b;1995). It had been previously concluded that the renal vascular beds possessed very few, if any, of the vasodilator subtype of the 5-HTI-like receptor, at which 5-carboxamidotryptamine is a potent agonist.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…By contrast, in the renal vascular beds, sumatriptan and 5-carboxamidotryptamine both produced marked vasoconstrictor responses, which were characterized by a very rapid recovery and evidence of a secondary vasodilatation (Cambridge et al, 1991a,b;1995). It had been previously concluded that the renal vascular beds possessed very few, if any, of the vasodilator subtype of the 5-HTI-like receptor, at which 5-carboxamidotryptamine is a potent agonist.…”
Section: Introductionmentioning
confidence: 99%
“…The vasoconstrictor 5-HTI-like receptors are selectively stimulated by the 5-HT,-like agonist, sumatriptan (Humphrey et al, 1988;Feniuk et al, 1989;Cambridge et al, 1995), whilst the tryptamine analogue, 5-carboxamidotryptamine, is a potent agonist at the vasodilator 5-HT,-like receptors (Saxena & Verdouw, 1985;Connor et al, 1986;Leff et al, 1987;Martin et al, 1987;Cambridge et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations